Rethinking Organizational Ethics: A Plea for Pluralism - van Oosterhout, J. (Hans) (Journal of business ethics, 2004)
This paper challenges a pervasive, if not always explicit assumption of the present state of theorising in business ethics. This is the idea that a workable theory of organizational ethics must provide a unified perspective on its subject matter. In this paper we will sketch the broad outlines of an alternative understanding of business ethics, which focuses on constraints on corporate conduct that cannot reasonably be rejected. These constraints stem from at least three different levels or spheres of social reality, i.e. the preconditions of a well-ordered society, the internal morality of economic activity and the preconditions of autonomous agency.